Peningkatan Hasil Belajar Bahasa Inggris pada Materi Descriptive Text Melalui Model Pembelajaran Kooperatif Tipe Student Teams-Achievement Divisions (STAD) - Tiara Putri Aishwaryadi (SAFE-Network, 2026)
This study aims to improve student learning outcomes by implementing the Student Teams Achievements Divisions (STAD) cooperative learning model in the English subject of Descriptive Text at SMKN 9 Padang. This method uses classroom action research (CAR), which is a deliberate observation of the teaching and learning process in the classroom. Before carrying out the main activities, the researcher first conducted initial observations as initial reflection material. The research subjects were 35 students in class X culinary 5. The results of the research that have been conducted, it can be concluded that the application of the Student Teams Achievements Divisions (STAD) cooperative learning model in the English subject of Descriptive Text is effective in improving student learning outcomes. This is evident from the increase in the percentage of student learning completion from 48.57% in cycle I to 88.57% in cycle II. This increase indicates that the STAD model is able to encourage active student participation, improve understanding, and help students who experience difficulties through group collaboration. In addition, structured learning and more intensive guidance from teachers also contribute to improving learning outcomes and student engagement during the learning process.